Tricobezoar associado à tricotilomania: relato de caso pediátrico - Bárbara Alves Deus; Ana Beatriz Ferreira de Souza Toge; Leonardo de Oliveira Antunes; Guilherme Diego de Oliveira Barbosa; Adriana de Oliveira Ribeiro dos Santos; João Carlos Diniz; Olavo Novaes Vieira Braga Ferraz; Henrique Vilela de Oliveira (Residência Pediátrica)
Case report of a 7-year-old female patient diagnosed with gastric trichobezoar requiring surgical intervention for removal. Psychic aspects related to obsessive-compulsive hair-pulling disorder were addressed, as well as diagnostic and treatment options. The relevance of this work is justified, since the condition is predominant in the pediatric age group and in most cases the first professional to contact this patient will be the pediatrician.